The solution is
.
Solution:
Given system of equations are
---------- (1)
---------- (2)
To solve the given system of equations by substitution method.
Let us take the equation (1) and find the value of y.
(1) ⇒ ![-3 x+y=4](https://tex.z-dn.net/?f=-3%20x%2By%3D4)
Add 3x on both sides of the equation, we get
⇒ ![y=4+3x](https://tex.z-dn.net/?f=y%3D4%2B3x)
Substitute y = 4 + 3x in equation (2), we get
![-9 x+5 (4+3x)=-1](https://tex.z-dn.net/?f=-9%20x%2B5%20%284%2B3x%29%3D-1)
![-9 x+20+15x=-1](https://tex.z-dn.net/?f=-9%20x%2B20%2B15x%3D-1)
Combine like terms together.
![-9 x+15x=-1-20](https://tex.z-dn.net/?f=-9%20x%2B15x%3D-1-20)
![6x=-21](https://tex.z-dn.net/?f=6x%3D-21)
Divide by 6 on both sides of the equation.
![$x=-\frac{21}{6}](https://tex.z-dn.net/?f=%24x%3D-%5Cfrac%7B21%7D%7B6%7D)
Divide the numerator and denominator by the common factor 3.
![$x=-\frac{21\div3}{6\div3}](https://tex.z-dn.net/?f=%24x%3D-%5Cfrac%7B21%5Cdiv3%7D%7B6%5Cdiv3%7D)
![$x=-\frac{7}{2}](https://tex.z-dn.net/?f=%24x%3D-%5Cfrac%7B7%7D%7B2%7D)
Now, substitute x value in y = 4 + 3x, we get
![$y=4+3\left(\frac{-7}{2} \right)](https://tex.z-dn.net/?f=%24y%3D4%2B3%5Cleft%28%5Cfrac%7B-7%7D%7B2%7D%20%5Cright%29)
![$y=4+\left(\frac{-21}{2} \right)](https://tex.z-dn.net/?f=%24y%3D4%2B%5Cleft%28%5Cfrac%7B-21%7D%7B2%7D%20%5Cright%29)
Take LCM of the denominators and make the same.
![$y=\frac{8}{2} +\frac{-21}{2}](https://tex.z-dn.net/?f=%24y%3D%5Cfrac%7B8%7D%7B2%7D%20%2B%5Cfrac%7B-21%7D%7B2%7D)
![$y=\frac{-13}{2}](https://tex.z-dn.net/?f=%24y%3D%5Cfrac%7B-13%7D%7B2%7D)
Hence the solution is
.